Description of Pseudomonas imrae sp. nov., carrying a novel class C β-lactamase gene variant, isolated from gut samples of Atlantic mackerel (Scomber scombrus) - Salvà-Serra, Francisco; Nimje, Priyank; Piñeiro-Iglesias, Beatriz; Alarcón, Leonarda Achá; Cardew, Sofia; Inganäs, Elisabeth; Jensie-Markopoulos, Susanne; Ohlén, Maria; Sailer, Hanna-Sophia; Unosson, Christel; Fernández-Juárez, Víctor; Pacherres, Cesar O.; et al. (Frontiers in Microbiology, 2025)
Three β-lactam resistant bacterial strains isolated from gut samples of wild Atlantic mackerel (Scomber scombrus) collected from the northern North Sea were characterized by polyphasic analyses. The strains were determined to belong to the genus Pseudomonas but could not be assigned to a known species. The nearly-complete 16S rRNA gene sequence showed the highest similarity (99.9%) to four different species, although partial rpoD sequence exhibited relatively low similarities to Pseudomonas proteolytica (93.4%) and other Pseudomonas spp. Genome sequencing and subsequent digital DNA–DNA hybridization (dDDH), average nucleotide identity (ANI) analysis and core genome analysis confirmed that these strains represent a novel species within the genus Pseudomonas. The three strains demonstrated ANIb values >99.5% with each other, confirming that all three strains (CCUG 74779T = CECT 30571T, CCUG 74780 and CCUG 74781) belong to the same genomospecies. Phylogenomic analysis confirmed that the strains form a distinct genomic clade, representing a novel taxonomic species, for which the name Pseudomonas imrae sp. nov., is proposed, with strain CCUG 74779T (=CECT 30571T) designated as the type strain. We report the complete genome sequence of the type strain of P. imrae sp. nov. and show that it carries a gene encoding a novel variant of a chromosomally-encoded class C β-lactamase, which has been designated as PFL-7.